New records of hygrobatid water mites from SE Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of ten new species - Smit, Harry; Pešić, Vladimir (Zootaxa, 2025)
New records are given of hygrobatid water mites of SE Australia. The following new species are described: Australiobates curvisetus sp. nov., A. dictyodermis sp. nov., A. papillatus sp. nov., A. tasmanicus sp. nov., Gondwanabates obtusus sp. nov., G. ninguis sp. nov., Kallimobates inusitatus sp. nov., Procorticacarus denticulatus sp. nov., Rhynchaustrobates capitalis sp. nov. and Rhynchaustrobates uncinatus sp. nov. The male of Australiobates ombates Cook and the female of Rhynchaustrobates truusae Smit are described for the first time.